Sorption of carbon dioxide on binderless beads of 13X - Silva, José A.C. (2014)
The sorption equilibrium of CO2 and CH4 in binderless beads of 13X zeolite has been investigated between 313 and 373 K and pressure up to 4 atm. The amount adsorbed of CO2 and CH4 is around 5.2 mmol/gads and 1.2 mmol/gads, respectively, at 313 K and 4 atm. Comparing these values with the ones in literature the value of CO2 is 20% higher than in CECA 13X binder pellets. The crystal diffusivity of CO2 measured experimentally by the ZLC technique is 5.8×10-15 m2/s and 1.3×10-15 m 2/s at 373 and 313 K, respectively. These values are in the same order magnitude of the ones measured by a frequency response and pulse chromatography techniques reported in literature. The ZLC desorption curves for CH4 were measured under an equilibrium regime and no kinetic data is obtained.